The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0104-66322010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evaluation of mature landfill leachate treatment by homogeneous catalytic ozonation

Abstract: -This study presents the results of a mature landfill leachate treated by a homogeneous catalytic ozonation process with ions Fe 2+ and Fe 3+ at acidic pH. Quality assessments were performed using Taguchi's method (L 8 design). Strong synergism was observed statistically between molecular ozone and ferric ions, pointing to their catalytic effect on OH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This can be explained by competition between different species of Fe 2+ ions and hydroxyl radicals (Equations (5)–(7)). A similar behavior was observed by Peixoto and Filho, [ 20 ] when studying the degradation of organic compounds in wastewater. Those authors found the optimal experimental conditions to be a high level of O 3 (0.6 g O 3 h –1 ) and low Fe 2+ (5 mg L –1 ).…”
Section: Resultssupporting
confidence: 85%
“…This can be explained by competition between different species of Fe 2+ ions and hydroxyl radicals (Equations (5)–(7)). A similar behavior was observed by Peixoto and Filho, [ 20 ] when studying the degradation of organic compounds in wastewater. Those authors found the optimal experimental conditions to be a high level of O 3 (0.6 g O 3 h –1 ) and low Fe 2+ (5 mg L –1 ).…”
Section: Resultssupporting
confidence: 85%
“…Leachate is classified as stabilized (mature), intermediate, or fresh (young) given BOD 5 /COD values of <0.2, 0.2-0.5, and >0.5, respectively (Robinson et al, 1983;Sun et al, 2010;Pilli et al, 2011). Some methods have been reported for the removal organics from landfill, such as biological treatment (aerobic, anaerobic and anoxic processes), physical methods (sedimentation, air stripping, adsorption, and membrane filtration) (Çeçen et al, 2003;Dehghani et al, 2007) and chemical methods (chemical precipitation (Lim et al, 2009;Kettunen et al, 1996), chemical oxidation (Zhao et al, 2010;Kurniawan et al, 2006), reverse osmosis, granular activated carbon (Peixoto et al, 2010), ion exchange R E T R…”
Section: Introductionmentioning
confidence: 99%
“…Scaling agent may absorb UV light or block penetration of UV light during the oxidation process, hindering the photolysis process and / or decreasing the production of ÁOH (Ghaly et al, 2001). Some examples of the compounds that absorb UV radiation are humic and fulvic acids (Peixoto and Filho, 2010), iron (200-400 nm), nitrate (230-240 nm), nitrite (300-310 nm), etc. (NWRI, 2000).…”
Section: Phasementioning
confidence: 99%
“…Physical-chemical and biological treatment are the common methods for landfill leachate treatment (Anfruns et al, 2013;Wu et al, 2004), especially the latter which is widely practiced due to its easy operation and low cost. However, the major drawback of biological treatment is that it is easily inhibited by toxic and recalcitrant compounds in landfill leachate, such as XOC and humic acids (Wang et al, 2012;Peixoto and Filho, 2010;Atmaca, 2009;Kim et al, 2001). Various authors also reported that biological treatment is only effective on immature leachate which has high biodegradability (Zhang et al, 2013;Wang et al, 2008;Kurniawan et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%